PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE STAD DI KELAS IV SD - Rusdian Fahriza; Arwin Arwin; Muhammadi Muhammadi (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study is aimed to describe improve learning out comes of social science by using model of two stay two stray in the fifth grade of elementary school, this study was carried oud in fifth grade of elementary school in SDN 16 Tanjung Aur Koto Tangah subdistrict Padang City, this study used classroom receach with qalitative and quantitative aproaches. The research subjects were 24 students from fifth grade of elementary school consist of 10 boys and 14 girls. Research prosedure consist of elanning, implementation, observation, and reflection. This research data is the result of lanning pissasment data, asessment of implementation that is the carning aipect of the teacher, learning aspect of the student and assasment of student learning activiti data.  The result shuwed an increase a) RPP of the cycle I was 85,7% (B)and the cycle II 92,8% (SB) the implementation of the aspect of the theacher in the cycle I was 76,58% (B)and the cycle II was 96,87% (SB), white the implementation of the aspect of the student in the cyce I was 73,38% (C), and the cycle II was 96,87% (SB). c) student learning activities in the cycle I was 53,90%(C), and the cycle II 82,02% (SB) the conclision os the study using two stay two stray can inprove the study out comes student learning activities of social scence in the tifth grade of elementary school in SDN 16 Tanjung Aur Koto tangah subdistrict, Padang city     Keyword : Learning outcomes; Social science; STAD